Increase in prominence of electrocardiographic J waves after a single dose of propofol in a patient with early ventricular repolarisation. (11th October 2013) - Takaishi, K.; Kawahito, S.; Yamada, H.; Soeki, T.; Sata, M.; Kitahata, H.
Summary J waves appear on an electrocardiogram as an elevation of the J point in the terminal portion of the QRS complex. J waves are often benign, but may be associated with malignant ventricular arrhythmias. In some cases, such problems appear to have been precipitated by propofol infusions. We observed a sudden increase in J waves and profound hypotension following a single intravenous dose of propofol in an 84‐year‐old woman with early repolarisation in the inferior ventricular wall. When early repolarisation (as shown by electrocardiographic J waves) is observed in the inferior ventricular wall pre‐operatively, patients should be carefully monitored. Myocardial ischaemia and the use of drugs that might worsen J waves should be avoided.